2021
DOI: 10.1002/jsfa.11601
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic effect of black soldier fly larvae on fungal community in a compost

Abstract: BACKGROUND Black soldier fly larvae (BSFL) offer very good prospects for the production of cheap and high‐quality dietary protein. This insect is able to consume low‐quality substrates, including food waste. The properties and safety of the compost obtained are largely determined by its microbiome. However, while the bacterial component of the BSFL‐compost microbiome has been much studied, little is known about its fungal component. In plant‐based rearing substrates both the biomass and the metabolic activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
8
2
Order By: Relevance
“…Although the microbial composition may change in this type of environment through time due to the composting process ( Jiang et al 2019 ), we found constancy in the dominance of Candida in most of the environments and larval guts. These results contradict previous analyses of the gut fungal community composition of BSF larvae that were fed on agricultural waste ( Boccazzi et al 2017 , Tanga et al 2021 ) and of the community composition of the compost environment that was treated with BSF ( Kuznetsova et al 2021 ). In these cases, the most abundant fungal genera in the BSF were Pichia and Cyberlindnera , which were not abundant in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although the microbial composition may change in this type of environment through time due to the composting process ( Jiang et al 2019 ), we found constancy in the dominance of Candida in most of the environments and larval guts. These results contradict previous analyses of the gut fungal community composition of BSF larvae that were fed on agricultural waste ( Boccazzi et al 2017 , Tanga et al 2021 ) and of the community composition of the compost environment that was treated with BSF ( Kuznetsova et al 2021 ). In these cases, the most abundant fungal genera in the BSF were Pichia and Cyberlindnera , which were not abundant in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Few studies have analyzed the fungal composition of BSF larvae; most of them studied laboratory colonies that were reared on different diets ( Boccazzi et al 2017 , Kuznetsova et al 2021 , Tanga et al 2021 ). This study presents a novel insight into the fungal composition of the BSF larval gut and its environment from samples that were collected from natural habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Although the microbial composition may change in the environment through time due to the composting process (17), the dominant fungal genus in most of the environments and larval guts was Candida. These results contradict previous analyses of the gut mycobiome composition of BSF larvae that were fed on agricultural waste (13) and of the mycobiome composition of the compost environment that was treated with BSF (18). In these cases, the most abundant fungal genus in BSF was Pichia , which was not an abundant genus in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…The study by Tanga et al (2021) proposed Pichia as a prevalent genus in BSFL guts across different diets including brewery waste. Furthermore, Kuznetsova et al (2021) reported that Pichia and Diutina dominated (99.9%) the residues after rearing BSFL for 5 days on food waste. We found Pichia to be present in BR, but only in low abundances (<0.1%).…”
Section: Discussionmentioning
confidence: 99%